APPLICATION OF THE GUIDED INQUIRY LEARNING MODEL WITH THE ASSISTANCE OF PhET TO IMPROVE HIGH SCHOOL STUDENTS' LEARNING OUTCOMES ON MOMENTUM AND IMPULSE - Br Sihotang, Marsheila Noverita; Sirait, Motlan (INPAFI (Inovasi Pembelajaran Fisika), 2023)
This study aims to find out how to improve student learning outcomes through the guided inquiry learning model with the help of PhET. The population in this study were class X students of SMA Negeri 7 Medan T.P 2022/2023 and the research samples were taken using a random sampling technique, namely class X MIPA 2 as the experimental class and X MIPA 5 as the control class. This research is a quasi-experimental research with Control Group Pretestt-Postestt Design. Data collection was carried out using the test method in the form of multiple choice tests which totaled 15 questions and student activity observation sheets. The results showed an increase in learning outcomes in the experimental class by 0.61 while in the control class it was 0.23. Student activity in the experimental class has increased and is stated with good (active) assessment criteria. Data analysis using the t test obtained that tcount>ttable = (8.39 > 1.669). So it can be concluded that the application of the guided inquiry learning model with the help of PhET can improve and have an influence on student learning outcomes on momentum and impulse material.